Scleroderma suthepense, a new ectomycorrhizal fungus from Thailand - Jaturong Kumla (2018)
A new species of earthball, described herein as Scleroderma suthepense, was found under Prunus cerasoides in Doi Suthep-Pui National Park, Thailand. Morphological characteristics indicate it belongs to section Scleroderma. Molecular analysis showed differences from previously described Scleroderma species. A description, illustration, and comparisons with related taxa are provided. © 2013. Mycotaxon, Ltd.